Detection of Infectious Adenoviruses in Environmental Waters by Fluorescence-Activated Cell Sorting Assay - Li, Dan (American Society for Microbiology (ASM), 2010)
Methods for rapid detection and quantification of infectious viruses in the environment are urgently needed for public health protection. A fluorescence-activated cell-sorting (FACS) assay was developed to detect infectious adenoviruses (Ads) based on the expression of viral protein during replication in cells. The assay was first developed using recombinant Ad serotype 5 (rAd5) with the E1A gene replaced by a green fluorescent protein (GFP) gene. Cells infected with rAd5 express GFP, which is captured and quantified by FACS. The results showed that rAd5 can be detected at concentrations of 1 to 10(4) PFU per assay within 3 days, demonstrating a linear correlation between the viral concentration and the number of GFP-positive cells with an r(2) value of >0.9. Following the same concept, FACS assays using fluorescently labeled antibodies specific to the E1A and hexon proteins, respectively, were developed. Assays targeting hexon showed greater sensitivity than assays targeting E1A. The results demonstrated that as little as 1 PFU Ads was detected by FACS within 3 days based on hexon protein, with an r(2) value greater than 0.9 over a 4-log concentration range. Application of this method to environmental samples indicated positive detection of infectious Ads in 50% of primary sewage samples and 33% of secondary treated sewage samples, but none were found in 12 seawater samples. The infectious Ads ranged in quantity between 10 and 165 PFU/100 ml of sewage samples. The results indicate that the FACS assay is a rapid quantification tool for detecting infectious Ads in environmental samples and also represents a considerable advancement for rapid environmental monitoring of infectious viruses.